Сергій Венгрженовський — маловідомий фольклорист із Поділля - Шалак, О.І. (Українська біографістика, 2010)
The work reveals the life of an original ethnologist and folklore specialist, a little known nowadays fellow-soldier of M. Lysenko and V. Antonovych — Sergiy Oleksandrovych Vengrzhenovskyi (1844–1913). The issues analysed in particular are his activity in Podilske Historical and Archaeological Society, his cooperation with M. Lysenko and with the editorial staff of «Kiyevskaya starina» periodical. The attention is concentrated at the specifi cs of collective activity of Mr. Vengrzhenovskyi and at the peculiarities of the recreation of Ukrainian folklore through Russian graphics of that time.